Hypothermic storage of Vietnamese stem cells from exfoliated deciduous teeth using crystalloid electrolyte solutions - Nguyen, Thi Sam; Ha, Tran Bao Chau; Do, Vinh Truong; Nguyen, Thi Thuy Ngan; Le, Thi Khanh Huyen; Nguyen, Thi Hiep; Nguyen, Doan Son; Chu, Hoang Ha (Vietnam Journal of Biotechnology, 2025)
Preserving the quality of mesenchymal stem cells (MSCs) during storage is crucial for their effective use in clinical applications, particularly in regenerative medicine and tissue engineering. This study investigated the effects of crystalloid electrolyte solutions on the hypothermic storage of Stem cells derived from Human Exfoliated Deciduous teeth (SHED) of Vietnamese, focusing on maintaining cell viability, proliferation, and adhesion capacities. Before storage, the cells were cultured and characterized for immunophenotypic markers, as well as osteogenic and adipogenic differentiation potentials. They were then stored in Lactated Ringer (LR) and Dextrose 5% in Lactated Ringer’s (D5LR) at 4 or 25°C for 2, 4, and 6 hours. Post-storage assessments revealed that LR at 4°C was the more effective solution, preserving cell viability and proliferation ability after 6 hours of storage. However, a significant reduction in cell adhesion was observed under these conditions. Conversely, cells stored in Dextrose 5% plus Lactate Ringer completely lost their capacity to proliferate and adhere to plastic surfaces, indicating its unsuitability for preserving cells. This study marks the first successful isolation of SHED from Vietnamese teeth, while also highlighting the potential of Lactate Ringer at 4°C as an optimal short-term storage solution, ensuring the functional integrity of SHED for clinical transplantation. This approach offers promising applications in the field of regenerative medicine, supporting advancements in therapeutic strategies for tissue repair and engineering.